Comparing the Use of Two Different Approaches to Assess Teachers' Knowledge of Models and Modeling in Science Teaching - Grace Carroll; Soonhye Park (MDPI AG, 2023)
Science teacher knowledge for effective teaching consists of multiple knowledge bases, one of which includes science content knowledge and pedagogical knowledge. With the inclusion of science and engineering practices into the national science education standards in the US, teachers' content knowledge goes beyond subject matter knowledge and into the realm of how scientists use practices for scientific inquiry. This study compares two approaches to constructing and validating two different versions of a survey that aims to measure the construct of teachers' knowledge of models and modeling in science teaching. In the first version, a 24-item Likert scale survey containing content and pedagogical knowledge items was found to lack the ability to distinguish different knowledge levels for respondents, and validation through factor analysis indicated content and pedagogical knowledge items could not be separated. Findings from the validation results of the first survey influenced revisions to the second version of the survey, a 25-item multiple-choice instrument. The second survey employed a competence model framework for models and modeling for item specifications, and results from exploratory factor analysis revealed this approach to assessing the construct to be more appropriate. Recommendations for teacher assessment of science practices using competence models and points to consider in survey design, including norm-referenced or criterion-referenced tests, are discussed.